Characterization of a MexAB-OprM efflux system necessary for productive metabolism of Pseudomonas azelaica HBP1 on 2-hydroxybiphenyl - Czechowska, Kamila; Reimmann, Cornelia; Van Der Meer, Jan Roelof (Frontiers in Microbiology, 2013)
Pseudomonas azelaica HBP1 is one of the few bacteria known to completely mineralize the biocide and toxic compound 2-hydroxybiphenyl, but the mechanisms of its tolerance to the toxicity are unknown. By transposon mutant analysis and screening for absence of growth on water saturating concentrations of 2-hydroxybiphenyl (2.7 mM) we preferentially found insertions in three genes with high homology to the mexA, mexB and oprM efflux system. Mutants could grow at 2-hydroxybiphenyl concentrations below 100 µM but at lower growth rates than the wild-type. Exposure of the wild-type to increasing 2-hydroxybiphenyl concentrations resulted in acute cell growth arrest and loss of membrane potential, to which the cells adapt after a few hours. By using ethidium bromide as proxy we could show that the mutants are unable to expel ethidium bromide effectively. Inclusion of a 2-hydroxybiphenyl reporter plasmid revealed that the wild-type combines efflux with metabolism at all 2-hydroxybiphenyl concentrations, whereas the mutants cannot remove the compound and arrest metabolism at concentrations above 24 µM. The analysis thus showed the importance of the MexAB-OprM system for productive metabolism of 2-hydroxybiphenyl.